Safety of COVID-19 vaccination in women undergoing IVF/ICSI treatment - Clinical study and systematic review - Chen, Huijun; Zhang, Xiaoli; Lin, Ge; Gong, Fei; Hocher, Berthold (Frontiers in Immunology, 2023)
It was suggested that vaccination in general might affect reproductive health. Safety of COVID-19 vaccination in women undergoing assisted reproductive techniques (ART) treatment is not well established. We performed a retrospective study including 536 women undergoing fresh embryo transfer after IVF/ICSI treatment in a huge IVF center in southern China to investigate the effect of COVID-19 vaccination on oocyte maturation, fertilization rate, blastulation rate, implantation rate, clinical pregnancy rate and miscarriage rate. In addition, we performed a systematic review of existing studies on the safety of COVID-19 vaccination in women undergoing ART treatment. In our study, 268 women received inactivated or recombinant COVID-19 vaccination and 268 controls were enrolled based on propensity score matching. We observed a decreased fertilization rate and signs for impaired oocyte maturation in vaccinated women. Besides our study, there were 15 studies analyzing the safety of COVID-19 vaccination in women undergoing ART treatment. For the mRNA vaccines, no adverse signals were reported concerning oocyte maturation, fertilization rate, blastulation rate, implantation rate, clinical pregnancy rate and miscarriage rate. In women being vaccinated with an inactivated vaccine, implantation rate, clinical pregnancy rate and miscarriage rate were not affected, whereas oocyte maturation and fertilization rate were impaired. In conclusion, vaccination against COVID-19 in women undergoing ART treatment seems to be safe especially for women getting mRNA vaccines. The effects on oocyte maturation and fertilization rate of inactivated and recombinant COVID-19 vaccinations might be a safety signal and need further investigation and independent confirmation.